Three new species of freshwater crabs of the genus Pseudothelphusa (De Saussure, 1857) (Crustacea: Decapoda: Pseudothelphusidae) from Mexico - Ojeda-Escoto, Juan Carlos; Villalobos, José Luis; Álvarez, Fernando (Zootaxa, 2017)
Three new species of freshwater crabs of the genus Pseudothelphusa (De Saussure, 1857) from south-central Mexico are described: Pseudothelphusa acahuizotla n. sp., P. ixtapan n. sp., and P. purhepecha n. sp. The new species are included in Pseudothelphusa due to a male gonopod with torsion and the presence of the characteristic mesial process and caudomarginal projection. Pseudothelphusa acahuizotla n. sp. is morphologically similar to P. belliana Rathbun, 1898, but can be distinguished by the relative size of the distal lobe of the caudomarginal projection and by the presence of a conical tooth on the caudal surface of the mesial process of the male gonopod. Pseudothelphusa ixtapan n. sp. is similar to P. dilatata Rathbun, 1898, and P. morelosis Pretzmann, 1968, and can be distinguished by a mesial process of the male gonopod with only one lateral tooth and an inferior margin with small teeth. Pseudothelphusa puerhepechae n. sp. exhibits a mesial process of the male gonopod with two triangular spines on its lateral margin, a character that with some variations is present in P. nayaritae Álvarez & Villalobos, 1994, P. rechingeri Pretzmann, 1965, P. lophophallus Rodríguez & Smalley, 1969, and P. parabelliana Álvarez 1989; but it can be distinguished by the separation and shape of the two spines of the mesial process and the shape of the lobes of the caudomarginal projection. With the new species described herein there are now 29 species in the genus Pseudothelphusa.